Integration of Islamic Moderation Values in Islamic Education Curriculum as an Effort to Prevent Radicalism Early on - Hasan, Moch Sya'roni; Solechan; Sunardi (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to describe the integration of Islamic moderation values ​​in the Islamic Religious Education (PAI) curriculum at Madrasah Ibtidaiyah (MI) Bahrul Ulum Nataan Gedongboyo Untung Lamongan as an effort to prevent early radicalization. The research method used is a qualitative approach with case studies, collecting data through in-depth interviews, participant observation, and document analysis. The research results show that MI Bahrul Ulum has made systematic efforts to integrate the values ​​of tawassuth (moderate), tawazun (balanced), and tasamuh (tolerant) in the PAI learning process. Innovations such as developing an Islamic Moderation Concept Map and using active learning methods and group discussions have increased students' understanding of diversity and tolerance. However, challenges such as limited appropriate learning resources and resistance from some parents need to be overcome. This research contributes to developing a moderation-oriented PAI curriculum model, emphasizes the importance of education in preventing radicalization, and enriches scientific knowledge in anti-radicalization education. These findings can be used as a reference for other educational institutions in developing curricula aligning with Islamic moderation values.